Menata Rumah yang Islami - Zien, Hafidz Zamroni; Kusumadewi, Tarranita (el Harakah: Jurnal Budaya Islam, 2011)
Prophet Muhammad in a hadith reveals that there are four things making people happy:  having shalihah  wife, spacious houses, comfortable vehicles, and good neighbors. A house as the inhabited buildings working as the activity base is one of the ways to form a society and Islam civilization. An Islamic house must be able to have two functions in life. First, the welfare of the world including: a sense of compassion (mawadah warahmah), ensuring children's education, creating hospitality (ukhuwah Islamiyah), forming the Muslim individual, supporting successful careers, and having health condition. Second, the welfare of the afterlife including: easy to implement the mahdah worship, muamalah process and able to keep its inhabitants from the things forbidden and makruh. An Islamic house is not always designed like mosques or houses which are full of Islamic ornaments, such as calligraphy, and more. An Islamic house is an efficient house which can be used to  dhikr to Allah, and to remember death. The house is not always facing the Qibla or the lavatory was not facing Mecca. An Islamic house is a house that allows occupants to stay and interact with others. Besides, the privacy of each person can also be maintained in it. It is then becoming the task of the architects to make Islamic houses. However, the most important thing of an Islamic house is that it does not isolate the occupants from the outside world. Further, it could create a better interaction and social relationship with its surroundings and neighbors. Nabi Muhammad dalam sebuah hadits mengungkapkan bahwa ada empat hal yang membuat orang bahagia: memiliki istri yang shalihah, rumah yang luas, kendaraan yang nyaman, dan tetangga yang baik. Rumah sebagai bangunan tempat tinggal yang berfungsi sebagai basis aktivitas merupakan salah satu cara untuk membentuk masyarakat dan peradaban Islam. Sebuah rumah islami harus mampu memiliki dua fungsi dalam kehidupan. Pertama, kesejahteraan dunia meliputi: rasa kasih sayang (mawadah warahmah), menjamin pendidikan anak, menciptakan keramahan (ukhuwah Islamiyah), membentuk individu muslim, mendukung karir yang sukses, dan memiliki kondisi kesehatan. Kedua, kesejahteraan akhirat yang meliputi: kemudahan dalam melaksanakan ibadah mahdah, proses muamalah dan mampu menjaga penghuninya dari hal-hal yang dilarang dan makruh. Sebuah rumah islami tidak selalu didesain seperti masjid atau rumah yang penuh dengan ornamen islami, seperti kaligrafi, dan lainnya. Rumah islami adalah rumah yang efisien yang dapat digunakan untuk berdzikir kepada Allah, dan untuk mengingat kematian. Rumah tidak selalu menghadap kiblat atau kamar mandi tidak menghadap Mekah. Rumah islami adalah rumah yang memungkinkan penghuninya untuk tinggal dan berinteraksi dengan orang lain. Selain itu, privasi setiap orang juga dapat terjaga di dalamnya. Hal inilah yang kemudian menjadi tugas para arsitek untuk membuat rumah-rumah islami. Namun, hal terpenting dari sebuah rumah islami adalah tidak mengisolasi penghuninya dari dunia luar. Selanjutnya dapat menciptakan interaksi dan hubungan sosial yang lebih baik dengan lingkungan dan tetangganya.